Survival analysis of time to abscission of blueberry leaves affected by Septoria leaf spot - Ojiambo, P.; Scherm, H. (Scientific Societies, 2005)
In the southeastern United States, Septoria leaf spot, caused by Septoria albopunctata, can result in premature defoliation of blueberry plants during summer and fall, thereby reducing yield potential for the following year. The effects of disease severity and leaf attributes (leaf age and leaf location in the canopy) on the dynamics (timing and extent) of defoliation were quantified in field plots of Premier rabbiteye blueberry (Vaccinium ashei) in 2002 and 2003. In each year, 50 shoots were selected for assessment in early spring, and all leaves on these shoots (n = 410 and 542 in 2002 and 2003, respectively) were monitored individually for disease progress and time of abscission at 3- to 10-day intervals throughout the season. In both years, disease progress was characterized by an exponential increase in disease severity up to late September, followed by a decline toward the end of the assessment period in late November. Defoliation was sporadic up to late August, followed by more rapid and sustained levels of leaf loss. Abscission of severely infected leaves could explain the decline in disease severity toward the end of the season. Final disease severity (i.e., disease severity on the last assessment date before leaf drop) was highest for leaves that abscised early and lowest for leaves that had not abscised by the end of the assessment period. Survival analysis revealed that older leaves (located on the lower halves of shoots) and leaves with high levels of disease (≥5 spots/leaf at the time of fruit harvest in mid-June) abscised significantly (P < 0.0001) earlier than younger leaves and leaves with lower disease severity. Relative to their respective reference groups, mean times to abscission were ≈2 weeks shorter for the older leaf group and ≈3 weeks shorter in the leaf group afflicted by high disease severity. When an accelerated failure time model was fitted to the data, the resulting parameter estimates indicated that each additional leaf spot present at harvest accelerated time to leaf abscission (expressed using late August as a starting point) by 1.9 and 4.5% in 2002 and 2003, respectively. Leaf location in upper or lower portions of the canopy had no significant effect on time to abscission (P > 0.05).